Regional development and urban growth in Bangladesh : a case for small and medium town in development - Mohit, Mohammad Abdul (Bangladesh National Geographical Association, 1989)
Besides four metropolitan urban areas - Dhaka, Chittagong, Khulna and Rajshahi,Bangladesh has 120 small and medium towns, 335 upazila centres and 5000 periodic markets. This means that there is one intermediate urban centre for every 691 villages, one upazila centre for every 256 villages and one periodic market for every 17 villages. Therefore, if proper policies are adopted for the development of intermediate urban centres within appropriate socieconomic and spatial framework, they would play the role of harbinger in the regional development of Bnagladesh.